Dampak lingkungan dan Arahan Pengelolaan dari Aktivitas Penambangan Ilegal Mineral Batuan di Desa Kota Donok Kabupaten Lebong - Yulian, Syahri; Barchia, M. Faiz; Santoso, Urip; Yurike, Yurike; Badarina, Irma (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
The purpose of this study was to determine how illegal rock mineral mining in Kota Donok Village, Lebong Regency, impacts the environment. The location of the study was Kota Donok Village in South Lebong District, Lebong Regency, and the type of research was descriptive qualitative. The community living in the mining environment of CV. Jang Riang in Kota Donok Village, South Lebong District, Lebong Regency, was the subject of the study. Furthermore, there were 6 parties responsible for environmental management of the rock mineral mining process in Lebong Regency, including CV. Jang Riang, the Head of Kota Donok Village, and the Energy and Mineral Resources (ESDM) Service of Bengkulu Province. Therefore, the total subjects were 34 people. Data collection was carried out through questionnaires, and data analysis was carried out through descriptive and SWOT analysis. The results of the study showed that illegal mining in Kota Donok Village, Lebong Regency had a very damaging environmental effect, damaging the local ecosystem and the social and economic aspects of the surrounding community. The biggest threats to environmental sustainability and human welfare in the area are aesthetic impacts, water pollution, and loss of ecological function. The management instructions for illegal rock mineral mining activities in Kota Donok Village, Lebong Regency are a defense strategy that aims to stop the rate of damage and reduce further risks by increasing supervision, conducting environmental mitigation, and encouraging the community to actively participate in environmental conservation. This method can be used to control, overcome, and repair the impacts of illegal mining